CABERGOLINE IN PRACTICAL MAMMOLOGY - I. V. Vysotskaya; T. Depuis; V. P. Letyagin (Медицинский совет, 2016)
Abnormal increase in prolactin hyperprolactinemia is one of the main signs of hypothalamic-pituitary-ovarian dysfunction. Consequently, the effect of dopamine on lactophores is attenuated resulting in their persistent hyperplasia and formation of functionally active microand macro-adenomas followed by an even greater prolactin level increase. According to statistics, prolactinomas are found in 25-30% of women with pathological hyperprolactinemia.